Effect of Rurality and Human Capital Resources in the Entrepreneurial Opportunity Identification Process - Kedmenec, Irena; Šebjan, Urban; Tominc, Polona (Naše gospodarstvo/Our economy, 2015)
In this paper, that is a country study of Slovenia, we tried to determine why individuals in rural residential areas are less likely to recognize entrepreneurial opportunities. Our results show that the increase in resources in human capital, consisting of education, skills, knowledge, and experiences in entrepreneurship, has a significant and positive effect on opportunity identification. For policy creators, our results suggest that policies focused on entrepreneurial education— especially education that would enable the acquisition of real-life entrepreneurial experiences and skills—are useful, especially in rural areas.